The Educated Citizen and Global Public-Health Issues: One Model for Integration into the Undergraduate Curriculum - Caron, Rosemary M. (Frontiers in Public Health, 2016)
The Educated Citizen Initiative proposes that an understanding of public-health issues is a core component of an educated citizenry and is essential to develop one’s societal responsibility. This initiative supports the Institute of Medicine’s recommendation that “all undergraduates should have access to education in public health.” Furthermore, the Liberal Education and America’s Promise (LEAP) framework developed by the Association of American Colleges and Universities supports the “integration of public-health education into general and liberal education with an aim to produce an educated citizenry.” The LEAP framework is implemented by teaching about the role of social determinants in a population’s health status; the significance of personal and social responsibility; and providing skills for inquiry, critical thinking, problem solving, and evaluation. This article describes one university’s experience in generating an educated citizenry cognizant of comprehensive public-health conflicts, thus contributing to both a local and global perspective on learning.